PENGARUH KUALITAS DAN HARGA TERHADAP KEPUASAN PELANGGAN DI HOTEL LOVINA INN NAGOYA - Susi Marni; Reno Okhtiyanto; Tina Arfah (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
The hospitality industry is an industry that is engaged in the service. Where pressing the services to compete competitively. This study aims to examine and analyze the quality and price to customer’s satisfaction in Hotel Lovina Inn Nagoya. This research is a quantitative study with a population. Of the population is taken 79 respondents sampled in this study. The sampling technique in this study is an non-probability sampling and sampling of this is by the way of accidental sampling. Spreading the questionnaire conducted for data collection. This study applied the method to obtain the results of the respondents hypothesis. This study measured with a 5-point Likert scale with which explains strongly agree to strongly disagree. The research data were processed using SPSS version 20 to help get the results of significant research. Through the F test obtained a value of 4,826 using 95% confidence level obtained value of F table = 3,117, It can be concluded that there is no effect between quality and price together.